Necesidad de incluir en el Código de la Niñez y Adolescencia una normativa que establezca un seguimiento sobre el destino que se da a las pensiones alimenticias acumuladas de los menores de edad - Chamba Tandazo, Mariana de Jesús (2015)
The Constitution now and always has been established as the fundamental and vital standard for the functioning of the state and therefore contains the entire legal system; mentioning a little history is in the twentieth, which had its best insufficiency of positivist system and its elements to ensure the rights. This work is based fundamentally the responsibility of parents for their children and the right of children to know the true parents and maintain relationships with them; preserve their own identity, while emphasizing the best interests of the child and adolescent as one of the principles prevailing in Ecuadorian legislation all based on compliance with the constitutional principles established in the Constitution of the Republic of Ecuador and the Code for Children and Adolescents. In Ecuador, for various reasons, nuclear families have been destroyed and, as a result of this, it has affected the situation of children / as and adolescents in our country, considering that from a first family separation, are abandoned and then the indifference of the parent / to be completely uninterested in their care, leaving them at the mercy of an increasingly consumerist and less caring society. The person who is in charge of the child or adolescent, inherited the noble and arduous task to protect him, but often without the means or financial resources to tend towards a healthy and full development of his personality. For these situations, and others, it is the latent choice of the mother (or father) under whose care the children / as are, to begin what was considered by many a tortuous path to request maintenance by judgment, what for; the / the parent or his / her family by mistake, or just quemeimportismo, has made both an economic and moral neglect the child or adolescent, can contribute to a pension. With the enactment of the Code for Children and Adolescents and the Constitution of the Republic in 2008, it is where the State guarantees the protection and integral development of children and adolescents, adopting administrative, economic and legal measures to ensure their effectiveness. During the development of this research it is legally shows that the procedure concerning the right to food and the failure of this is inconsistency with the principles of judicial economy and simplification enshrined in the Constitution of the Republic. This research is by conducting a field study regarding the problem to investigate, to what has been obtained the judgment of a panel of judges of the specialized units Third of Children and teens who have jurisdiction in matters of minors through the interview technique and attorneys in free practice and our distinguished judges, using the technique of the survey, who have expressed their views and opinions regarding the proposed theme. The study of drawing conclusions, recommendations and the respective proposal for legal reform stating an Article unnumbered in Title V of Food Law in Chapter I of the Organic Food Law Code of Childhood and Adolescence is complemented